Radar Absorber Composite Graphene Oxide/Magnetite/Zinc Oxide in Polypyrole Matrix - Allodya Nadra Xaviera; Vania Agatha Nareswari; Dea Dwi Ananda; Hazzha Azzahra; Thessa Ocatvia Joyetta Tarigan; Tiara Rizki Yulita; Nugroho Adi Sasongko; Rahmat Basuki (Sorption Studies, 2025)
The development of stealth technology in modern defense systems demands superior radar absorbing material (RAM) innovation. This study aims to synthesize and characterize Fe₃O₄/ZnO modified carbon-based RAM composites in a polypyrrole (PPy) matrix using graphite oxide (GiO). The composites were synthesized via a modified Hummer method as well as a one-pot technique, and characterized using FTIR, XRD, SEM-EDX, and VNA. The FTIR characterization results showed that the C=C peak decreased in intensity after the oxidation process, indicating the breaking of the aromatic double bond and the formation of new functional groups such as C–O and C=O. This change was detected in both pGiO and kGiO samples. XRD data showed a shift in the main peaks to 2θ = 11.25° and 42.20° for pGiO and 2θ = 11.56° and 42.40° for GiO-k, respectively. This shift indicates the formation of a more amorphous graphite oxide structure compared to the original graphite.The results show that GiO/Fe₃O₄/ZnO has the highest reflection loss value of -9.20 dB at 10.91 GHz (GiO-p/Fe₃O₄/ZnO 66%-PPy) with an absorption value of 88.03% and rGO/Fe₃O₄/ZnO/PPy the highest RL value reached -7.51 dB at 11.57 GHz (rGO-k/Fe₃O₄/ZnO 66%-PPy) with an absorption value of 82.21%. This research proves that Fe3O4/ZnO modified carbon-based composites in a polypyrrole matrix have high potential as an efficient radar absorbing material and can support the needs of domestic defense technology.